IMPROVING STOCK INVESTMENT PERFORMANCE THROUGH FUNDAMENTAL ANALYSIS: SEMINAR FOR A STOCK INVESTOR COMMUNITY - Dananjaya, Yanuar; Napitupulu, Priskilla E.E. (Faculty of Economics and Business Universitas Pelita Harapan, 2024)
This community service was conducted in the form of a webinar delivered to stock investors. Indonesian stock investors face the problem of high percentage of investor experiencing negative return. This is strange as Indonesian stock market index (IHSG) generally trend upward from year to year. One of the possible causes is the inability of investors to perform good analysis of stocks. Thus, the topic of stock fundamental analysis is chosen for the webinar. In the webinar, various topics of fundamental analysis such as value investing, how to identify cheap stocks, how to measure company performance, how to understand risk, are explained and discussed. It is expected that by improving the investor’s ability to conduct fundamental analysis, investors can earn higher return for their investment. Judging from the feedback of webinar participant, the webinar was conducted well and very useful for investors.